Dynamic Monitoring of sTREM-1 and Other Biomarkers in Acute Cholangitis - Jiahui Jiang; Xiaolei Wang; Tongtong Cheng; Mingyue Han; Xinxin Wu; Haitong Wan; DaojunYu (Mediators of Inflammation)
Background. Sepsis is a common complication of acute cholangitis (AC), which is associated with a high mortality rate. Our study is aimed at exploring the significance of white blood cell (WBC), C-reactive protein (CRP), procalcitonin (PCT), soluble triggering receptor expressed on myeloid cells 1 (sTREM-1), and temperature (T) alone or combined together in early identification and curative effect monitoring of AC with or without sepsis. Methods. 65 consecutive cases with AC and 76 control cases were enrolled. They were divided into three groups: Group A (AC with sepsis), Group B (AC without sepsis), and Group C (inpatients without AC or other infections). The levels of WBC, CRP, PCT, sTREM-1, and temperature were measured dynamically. The study was carried out and reported according to STARD 2015 reporting guidelines. Results. CRP had the highest AUC to identify AC from individuals without AC or other infections (AUC 1.000, sensitivity 100.0%, specificity 100.0%, positive predictive value 100.0%, and negative predictive value 100.0%). Among various single indexes, PCT performed best (AUC 0.785, sensitivity 75.8%, specificity 72.2%, positive predictive value 68.7%, and negative predictive value 78.8%) to distinguish sepsis with AC, while different combinations of indexes did not perform better. From day 1 to day 5 of hospitalization, the levels of sTREM-1 in Group A were the highest, followed by Groups B and C (P<0.05); on day 8, sTREM-1 levels in Groups A and B declined back to normal. However, other index levels among three groups still had a significant difference on day 10. Both in Groups A and B, sTREM-1 levels declined fast between day 1 and day 2 (P<0.05). Conclusions. CRP is the best biomarker to suggest infection here. PCT alone is sufficient enough to diagnose sepsis with AC. sTREM-1 is the best biomarker to monitor patients’ response to antimicrobial therapy and biliary drainage.